Transportability Improvement of a Gas–Liquid Rotodynamic Pump Using the Two-Step Multi-Objective Optimization Strategy - Zhang, Wenwu; Zhu, Baoshan; Zi, Dan; Ma, Zhe; Wang, Fujun (Frontiers in Energy Research, 2022)
The development of multiphase pumps is restricted because of low efficiency and poor mixing transportation capacity. In this study, a two-step multi-objective optimization design system for a multiphase pump is constructed using a three-dimensional (3-D) design theory and multi-objective optimization techniques. The transportability improvement for the pump impeller is achieved by implementing the optimization variables of its geometry and blade loading, and the optimization objectives containing the pump efficiency and gas uniformity. The optimal results of impeller geometry show that the blade wrap angle and control parameters of the hub have remarkable effects on the pump efficiency and gas uniformity. The optimal results of impeller blade loading show that the pump efficiency is improved if the impeller with large loading at the leading edge, large slope at middle part and large negative high-pressure edge angle. The gas uniformity is improved if the hub loading at the middle and trailing parts is larger than the shroud loading. Compared to the original test impeller, the pump efficiency with the impeller T-Opt1 and the gas uniformity at the impeller outlet are improved by 10.81% and 6.91%, respectively. The maximum fluctuation amplitudes in T-Opt1 and its corresponding guide vane are reduced by 0.61% and 67.76%, respectively.